Out-of-pocket health expenditure for poor and non-poor older adults in Colombia: composition and trends (2015)
Colombia is a middle income country with a growing older adult population and the only country in Central and South America with Universal Health coverage insurance. The purpose of this article is twofold. First, it describes a simple methodology to estimate Out-of-Pocket (OOP) health spending by line items using the Colombian Living Standard Measurement Survey (LSMS). Second, it describes the composition of such spending and shows recent trends in OOP health expenditures between poor and non-poor older adults using three waves of the same survey. Annual OOP on health spending, as percentage of Gross Domestic Product (GDP), was 2.87, 2.59 and 2.33% for those years respectively. Personal hygiene represents the largest line item, followed by over-the-counter (OTC) drugs, dentistry services and transportation to the point of care. At the per-capita level, OOP spending on health care for older adults is also low, representing 3% of the legal monthly minimum wage for poor older adults and 9% for non-poor older adults. Nonetheless, a look at the composition of the OOP reveals that older adults are at a disadvantage due to the fact that OTC drugs represent the biggest share of their spending, 44% for the poor and 31% for the non-poor.